Validity of a mobile-based specific test to estimate metabolic thresholds in boxers - de Oliveira, L. B.; Sant` Ana, J.; Freccia, G. W.; Coswig, V. S.; Diefenthaeler, F. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
This study aimed to investigate the validity of a boxing-specific test to predict anaerobic threshold (AT) using the heart rate deflection point (HRDP) in boxing athletes with mobile technology. Ten male boxing athletes performed the boxing-specific incremental test (TBOX). Maximal heart rate (HRMAX), HRDP, pace, maximal punch frequency (FPMAX), and punch frequency relative to HRDP (FPAT) were measured. Participants also performed an incremental running test on a treadmill (IT) as a reference test. Paired t-tests were performed to verify differences between the mean values of HRMAX and HRDP during TBOX and IT. Pearson linear correlation was applied to test correlations and the Bland and Altman visual analysis was used to verify the level of agreement. A significant level of p < 0.05 was adopted. The average HRDP was 174 ± 7 bpm, which corresponded to 92% of the observed HRMAX. FPAT and FPMAX presented values between 39 ± 4 and 73 ± 8 blows, respectively. No differences were found, and strong correlations were evidenced between TBOX and IT for HRMAX (p = 0.281; r = 0.73) and heart rate response related to HRDP (p = 0.096; r = 0.85). The 95% limits of agreement for the differences between TBOX and IT for HRMAX should be considered with bias by 2.1 ± 9.7 found between -7.65 and 11.85, as well as the 95% limits of agreement for the differences between TBOX and IT for HRDP with bias -2.3 ± 7.68 found between -9.98 and 5.38. HRMAX and HRDP obtained during TBOX leads us to infer that the test was well founded to estimate parameters associated with the aerobic power and aerobic capacity of boxing athletes. In addition, TBOX shows significant applicability for the aerobic assessment of boxers based on real competition movements and can be useful to determine and control training intensities.